Medication Administration and Knowledge Retention in Baccalaureate Nursing Students - Pamela Treister; Donna Darcy (Journal of Systemics, Cybernetics and Informatics, 2016)

(untitled)
A quality improvement project was undertaken in order to assist the undergraduate baccalaureate nursing students in knowledge retention for medication administration during their senior semester in nursing school. Two specific changes in curriculum were implemented in order to assist these undergraduate baccalaureate nursing students at a suburban private university in New York. Simulation and the incorporation of competency by rubrics were implemented in the spring semester of junior year, which led to an increased knowledge retention during the fall semester of the senior year. This article discusses the advantages and challenges of using technology, how change occurred in the junior year semester and the effects it had on the senior nursing student's retention of medication administration knowledge.